Analysis Of The Use Of Microfillers In Cement Materials - Islomov Mirshodbek Isomiddinovich; Safarova Ruxshona Ulug‘bek qizi; Bekov Ulug‘bek Safarovich (Academia One, 2025)
The article analyzes the influence of various microfillers on the properties of cementcontaining materials using the example of the most effective microfillers - highly active metakaolin, microsilica, fly ash and aluminosilicates
Keywords: highly active metakaolin; microsilica; fly ash